Psychometric Properties of the Russian Version of the Perceived Stress Scale (PSS-4, 10, 14) - A.A. Zolotareva (Клиническая и специальная психология, 2023)
This study was aimed to adapt and analyze the psychometric properties of the Perceived Stress Scale (PSS) in its full (PSS-14) and two short versions (PSS-10, PSS-4). Psychometric analysis of the Russian versions of the PSS was performed on a sample of 558 Russian-speaking respondents, including 278 men and 280 women aged 18 to 78 (M=48.10; SD=13.91). The participants completed the Russian versions of the PSS and Depression, Anxiety, and Stress Scale-21 (DASS-21). The factor validity of the PSS was assessed by exploratory and confirmatory factor analyses, which indicated a two-factor structure, including distress factor (direct-item scale) and coping factor (reverse-item scale). Perceived stress scores correlated positively on all versions of the PSS with psychological distress scores on the DASS-21. The internal reliability of the adapted scales was revealed by α-Cronbach’s coefficients, whose values were α=0.841 for PSS-14, α=0.831 for PSS-10, and α=0.703 for PSS-4. The known-groups validity was confirmed by the fact that women scored higher on perceived stress on the PSS-14, PSS-10, and PSS-4. In conclusion, the PSS-10 is preferred for research tasks and the PSS-4 can be used in time-limited testing conditions.